A Study on the Satisfaction of Agripreneurs towards Institutional Support with Reference to Bangalore rural District (International Journal of Food and Nutritional Sciences, 2023)
Agribusiness is the business of agricultural production, including farming, processing, distribution and marketing of agricultural products. It encompasses a range of activities from the production of crops and livestock to the manufacturing of food and other agricultural products, such as textiles, biofuels, and pharmaceuticals. Agribusiness also includes the supply of inputs, such as fertilizers, seeds, and machinery, and the provision of services such as consulting, credit, and insurance. Also Agribusiness is a vital sector for many countries contributing to economic development. Institutional support in nascent stage like planning support, production support, marketing and other support for agribusiness can play a crucial role in promoting sustainable agricultural practices improving farmers' access to resources and enhancing their productivity and profitability. Further institutional support for agriculture can come from a variety of sources including research institutions, extension services, agricultural finance and insurance institutions, government policies and programs and international organizations.